Tokens of love, loss and disrespect, 1700-1850 - Lloyd, Sarah; Lloyd, Sarah; Millett, Timothy; Millett, Timothy (Paul Holberton Publishing, 2022)
Coins from the 18th and early 19th centuries are physically and visually intriguing. In addition to their monetary uses, they were repurposed to communicate private and public messages - from ad hoc scratchings and punch marks to full-scale re-engraving of surfaces. This book aims to give 21st-century readers insight into that experience and to the many unofficial purposes these objects served.0Drawing on the largest extant collection of defaced coins and tokens, this publication brings together for the first time the full-range of expertise required to understand the phenomenon, with contributions from 11 scholars and collectors. It focuses on a significant period in British history, when modification expressed political commentary, commercial activity, familial and emotional commitment, personal identity and life history. It will examine the coins and tokens themselves and look at who modified them, where, why and how. The circumstances of the coins' subsequent survival is explained, and each aspect will be set in its specific historical contexts